Atypical patterns of segregation of familial enlargement of the vestibular aqueduct - Muskett, Julie A. (Laryngoscope, 2015)
OBJECTIVE: Hearing loss and enlargement of the vestibular aqueduct (EVA) can be inherited as an autosomal recessive trait caused by mutant alleles of the SLC26A4 gene. In some other families, EVA does not segregate in a typical autosomal recessive pattern. The goal of this study was to characterize the SLC26A4 genotypes and phenotypes of extended families with atypical segregation of EVA. STUDY DESIGN: Prospective study of cohort of families ascertained between 1998 and 2014 at the National Institutes of Health Clinical Center. METHODS: Study subjects were members of eight families segregating EVA in at least two members who were not related as siblings. Evaluations included pure-tone audiometry, temporal bone imaging, SLC26A4 nucleotide sequence analysis, SLC26A4-linked marker genotype and haplotype analysis, and pedigree analysis. RESULTS: One family had members with EVA caused by different etiologies, and two families had pseudo-dominant inheritance of recessive mutations of SLC26A4. In five families, the etiology remained unknown and could include inheritance of mutant alleles at another genetic locus, non-genetic influences, or a combination of these factors. CONCLUSIONS: Familial EVA can demonstrate a variety of atypical segregation patterns. Pseudo-dominant inheritance of SLC26A4 mutations or recessive alleles of other hearing loss genes may be more likely to occur in families in which deaf individuals have intermarried. The etiologic basis of atypical segregation of EVA without detectable SLC26A4 mutations remains unknown. Future studies of these families may reveal novel genes for EVA.